1998
DOI: 10.1097/00003246-199804000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and posttraumatic stress disorder in survivors of the acute respiratory distress syndrome

Abstract: Long-term survivors of ARDS describe a good overall health-related quality of life. Major impairments in mental health domains of health-related quality of life are associated with the development of posttraumatic stress disorder and are a possible result of traumatic experiences during ICU therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
309
1
14

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 547 publications
(353 citation statements)
references
References 29 publications
21
309
1
14
Order By: Relevance
“…In fact, it has been demonstrated that after recovery in the ICU, a higher number of patients reported symptoms, such as anxiety, pain, and nightmares, that can turn into chronic psychiatric disorders and depression. In 1998, Schelling et al 36 found an incidence of posttraumatic stress disorder of 28% in survivors of ALI/ARDS after 5 y. In general, the prevalence of posttraumatic stress disorder changes depending on the time of assessment, and it was found to be higher at ICU discharge.…”
Section: Neuropsychological Disabilitymentioning
confidence: 99%
“…In fact, it has been demonstrated that after recovery in the ICU, a higher number of patients reported symptoms, such as anxiety, pain, and nightmares, that can turn into chronic psychiatric disorders and depression. In 1998, Schelling et al 36 found an incidence of posttraumatic stress disorder of 28% in survivors of ALI/ARDS after 5 y. In general, the prevalence of posttraumatic stress disorder changes depending on the time of assessment, and it was found to be higher at ICU discharge.…”
Section: Neuropsychological Disabilitymentioning
confidence: 99%
“…The incidence of PTSD in patients discharged from ICU was examined by Schelling [2]. This questionnaire study of 87 survivors of critical illness used a self-report scale of PTSD, the PTSD 10 Inventory [3].…”
mentioning
confidence: 99%
“…Sowohl auf einer Symptomals auch auf einer Störungsebene zeichnet sich für diese affektive Morbidität eine oft langwierige Persistenz ab. Diese wird in einigen prospektiven Longitudinalstudien mit sukzessiven Messzeitpunkten für die ersten Monate nach überstandener intensivpflichtiger Erkrankung [4,5] bis zu 1 und 2 Jahren im weiteren Verlauf [6][7][8], in einigen Follow-up-Studien auch über einen sehr viel längeren Zeitraum nachgewiesen [9,10].…”
Section: Prävalenz/inzidenzunclassified
“…eine unzureichende Analgesie müssen als eigenständiger Risikofaktor für eine PTSD oder Depression gewertet werden [43]. Schlecht kontrollierte Schmerzen können nach schwerwiegenden Verletzungen, Verbrennungen oder aber nach großen Operationen vorübergehend, zuweilen auch längerfristig auf Intensivstationen vorliegen und traumatisch wirken [9]. In einer prospektiven Studie wies die Einweisung auf eine chirurgische [24].…”
Section: äTiopathogenetische Faktorenunclassified